An observational synthesis of the Taurid meteor complex. Issue 2 (16th February 2022) - Egal, A; Brown, P G; Wiegert, P; Kipreos, Y
ABSTRACT: We provide an overview of the observational properties of the four major Taurid showers, namely the Northern and Southern Taurids (#017 NTA and #002 STA), the β Taurids (#173 BTA), and the ζ Perseids (#172 ZPE). Analysing more than two decades of meteor observations from visual, optical, and radar measurements, we present the Taurids average activity, annual variations in strength, radiant drift, and orbital variations as a function of solar longitude and particle size. The Taurid showers are detected over several weeks in the spring and autumn, but their annual activity level is generally low (less than 15 visual meteors per hour). We find the STA to be pre-dominant in autumn, while its twin, the ZPE, dominates over the BTA in spring. Due to their long duration, the position of each shower's radiant and orbital elements are variable with time. Optical measurements have previously recorded enhanced STA activity and increased fireball rates caused by the return of a swarm of meteoroids trapped in the 7:2 mean motion resonance with Jupiter. However, we find no presence of the swarm in radar data, suggesting that small meteoroids are removed from the resonance faster than fireball-producing meteoroids. We also find the STA to be enriched in smaller particles early in their activity period. The differences we identify in our analysis between the showers at different particle sizes provide strong observational constraints to future dynamical modelling of the Taurid Meteoroid Complex.